Deformation Quantization and Representations of the Real Rotation Group - Nable, Job (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Excerpt In this paper we present concrete computations of representations of the real rotation group SO(3,R) arising from deformation quantization of its coadjoint orbit Ωξ = S^2.